Roles of Music-Making in the Process of Cross-Cultural Adaptation: A Case of International Students in Wrocław - Alptekin, Emre Can (2022)
With the intensifying flow of academically motivated people between countries, the significance of research on cross-cultural adaptation increases. Although the problems and difficulties caused by cultural differences have been researched extensively, this research focused on a common practice among different cultures: participative music-making in an intercultural context. Therefore, the current study explores how participative music-making shapes international students’ cross-cultural experiences in Wrocław. For this purpose, the relevance between international students’ cross-cultural adaptation and music-making as a social activity in Poland is examined. The required data were gathered through in-depth interviews with six students from various countries who made music as a collective activity during their transnational accommodation. The collected data is analysed by the inductive coding approach to explore the commonalities in the international students’ experiences. Findings concluded that collective music-making shapes music-maker students’ cross-cultural experiences by not merely helping them gain a specific social network but also contributing to their financial income and mood states, and finally, privileged behaviour by the host country members towards these students.
Keywords: music-making; sociocultural adaptation; psychological adjustment; culture learning theory; cross-cultural transition; social network